Revascularization Outcomes in Patients With Acute Limb Ischemia and Active Neoplastic Disease. (February 2021) - Argyriou, Angeliki; Kafetzakis, Alexandros; Saratzis, Athanasios; Huasen, Bella; Coscas, Raphaël; Renard, Regis; Bisdas, Theodosios; Torsello, Giovanni; Tsilimparis, Nikolaos; Calderbank, Tom; Stavroulakis, Konstantinos
Purpose: To report the outcomes of surgical (ST), endovascular (ET), and hybrid (HT) treatment in cancer patients with acute limb ischemia (ALI). Materials and Methods: A multicenter retrospective registry collected 139 patients (mean age 72.3±12.4 years; 73 men) with ALI and active malignancy treated by ET (41, 29%), ST (70, 51%), or HT (28, 20%) in 7 European centers between July 2007 and February 2019. In 22 cases (16%) ALI was the first manifestation of the malignancy. Lung cancer was the most common diagnosis (38, 27%). The primary composite outcome was amputation-free survival (AFS). Overall survival, amputation-free time (AFT), and reintervention-free time (RFT) were also assessed. Cox regression analysis was applied to identify independent risk factors for the primary and secondary outcomes. Results are presented as the hazard ratio (HR) and 95% confidence intervals (CIs). Results: ET was associated with improved 12-month AFS compared with both ST (HR 2.27, 95% CI 1.20 to 4.28, p=0.002) and HT (HR 2.14, 95% CI 1.09 to 4.18, p=0.008). ST (HR 2.50, 95% CI 1.19 to 5.53, p=0.003) and HT (HR 3.10, 95% CI 1.45 to 6.65, p<0.001) were related to an increased risk for mortality compared with ET. At 12 months, the AFT was similar between the 3 groups (ET vs ST: HR 1.52, 95% CI 0.51 to 4.53, p=0.45 and ET vs HT: HR 1.21, 95% CI 0.36 to 4.11, p=0.73). The 12-month RFT also did not differ significantly between the 3 treatment options (ET vs ST: HR 1.10, 95% CI 0.49 to 2.46, p=0.79 and ET vs HT: HR 0.51, 95% CI 0.22 to 1.17, p=0.19). ST and/or HT increased the risk for the major amputation and/or death (HR 1.76, 95% CI 1.05 to 2.05, p=0.03), while Rutherford class I ischemia (HR 0.12, 95% CI 0.02 to 0.90, p=0.04) and previous vascular interventions on the index limb (HR 0.55, 95% CI 0.32 to 0.97, p=0.04) showed a protective effect. Conclusion: In patients with ALI and active malignant disease, ET was associated with increased AFS and overall survival compared with both ST and HT, while the limb salvage and reintervention rates were comparable among the 3 groups.